2002
DOI: 10.1086/341068
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Deletions Suggest a Phylogeny for theMycobacterium tuberculosisComplex

Abstract: To better understand the evolution of the Mycobacterium tuberculosis complex, subspecies were tested for large sequence polymorphisms. Samples with greater numbers of deletions, without exception, were missing all the same regions that were deleted from samples with lesser numbers of deletions. Principal genetic groups based on single-nucleotide polymorphisms were restricted to one of the deletion-based groups, and isolates that shared genotypes based on molecular epidemiological markers were assigned almost e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
186
0
8

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 222 publications
(213 citation statements)
references
References 27 publications
19
186
0
8
Order By: Relevance
“…A study by Behr & Small (1999) that identified deletion events in M. bovis BCG has elicited information on the evolution of BCG strains. Similar evolutionary insights into the origin of the seal bacillus have been gained by using comparative genomic technologies that were described previously (Brosch et al, 2002;Mostowy et al, 2002). In both studies, the seal strain was separated from classical M. bovis by at least six deletions.…”
Section: Dna Spoligotypingmentioning
confidence: 64%
“…A study by Behr & Small (1999) that identified deletion events in M. bovis BCG has elicited information on the evolution of BCG strains. Similar evolutionary insights into the origin of the seal bacillus have been gained by using comparative genomic technologies that were described previously (Brosch et al, 2002;Mostowy et al, 2002). In both studies, the seal strain was separated from classical M. bovis by at least six deletions.…”
Section: Dna Spoligotypingmentioning
confidence: 64%
“…Further evidence for the independence of the caprine mycobacterial isolates from M. bovis is derived from two recent studies that have examined the evolution of the M. tuberculosis complex (Brosch et al, 2002;Mostowy et al, 2002). Both these studies tested two different and representative sets of isolates of the M. tuberculosis complex (n=100 and n=66, respectively) from different hosts and countries.…”
mentioning
confidence: 99%
“…In this study, (Rv1970) gene was used to differentiate M. tuberculosis from the other of M. tuberculosis subspecies, LprM (Rv1970) is a gene lies in the RD7 region 27,28 . In prior studies, PCR analysis revealed RD7 to be present in all of the tested M. tuberculosis but not in the evaluated M. microti, M. bovis, M. bovis BCG, and M. caprae strains 29,30 . Primers were used to amplify Rv1970 (mce3E) and the PCR results were positive for 40(80%) of isolates (Figure not shown).…”
Section: Methodsmentioning
confidence: 86%